Physicochemical characterization of white, yellow and purple maize flours and rheological characterization of their doughs - Moreira, R. (J Food Sci Technol, 2015)
White, yellow and purple maize flours were obtained after dried kernels milling with two different sieves (200 and 500 μm). Hygroscopic characteristics, particle size distribution, colour and total starch and damaged starch (DS) of flours were determined. Maize flour doughs were obtained by mixing of flour and water in a laboratory kneader (Mixolab®) at constant dough consistency (1.10 ± 0.07 Nm). Dough properties like water absorption (WA), development and stability times were determined. Rheological characterization was carried out at 30 °C by means of oscillatory frequency sweep (1–100 rad s(−1)) at 0.1 % strain and creep (50 Pa, 60 s) - recovery (0 Pa, 180 s) tests using a controlled stress rheometer. No significant differences were observed among water desorption isotherms of maize varieties and Halsey model was satisfactorily employed. Under the same milling conditions, white maize flours showed higher average particles size than purple and yellow maize flours. A model to predict flours colour involving colour parameters of the particle size fractions is proposed. Flours obtained with smaller particle size showed higher DS content and WA. For tested doughs, the mechanical spectra showed that elastic component was dominant over the viscous one. Damping factor varied slightly with angular frequency. Moduli values depended on average particle size and WA of dough. Creep-recovery data were satisfactorily fit with Burgers model. Instantaneous creep compliance varied with the same trend than elastic modulus. Viscoelastic creep compliance increased linearly with WA of the tested doughs and, at constant average flour particle size, increased with increasing DS.